Point contact Andreev reflection and tunneling spectroscopy using high-field superconductors, topological insulators and compensated ferrrimagnets - Borisov, Kiril (Trinity College (Dublin, Ireland). School of Physics, 2017)
Spin electronics is a young and thriving research and technology field which relies more on the spin of the electron rather than its charge. The tunneling magnetoresistance and giant magnetoresistance effects have been already utilized in novel non-volatile magnetic memories and highly sensitive magnetic sensors. The improvement of the current magnetic storage and detection devices depends critically on integration of new compositions with enhanced magnetic and magneto-transport properties. The data retention and further scalability depend on materials with higher anisotropy and lower magnetization. A critical parameter is the spin polarization, because the tunneling magnetoresistance and the giant magnetoresistance effects depend on it, so does the switching efficiency through the spin-transfer torque. Therefore, novel materials with higher anisotropy, lower magnetization and higher spin polarization are sought-after. Among the spin polarization measurement techniques, point contact Andreev reflection has established itself as a reliable, straight-forward and swift method. This thesis focuses on the technique of point contact Andreev reflection (PCAR) for spin polarization measurements in new materials like topological insulators and disorder ferromagnetic compositions. Systematic effort is made to extend the technique of Andreev reflection to high magnetic field in order to determine the sign of the spin polarization. The integration of novel compensated half-metallic ferromagnetic composition in magnetic tunnel junctions is presented as well. The thesis starts with a brief theoretical overview of the spin electronic field in Chapter 1. The main devices and physical effects are described. The Blonder-Tinkham-Klapwijk (BTK) theory, which is the most widely used one for data analysis of PCAR experiments is outlined as well. All measurement techniques and equipment used during this work are described in the experimental Chapter 2. Topological insulators have become an intense scientific area during the last decade after the realization of Quantum Spin Hall effect by Molenkamp’s group in 2007. Later, topological insulating state has been achieved in single materials with high spin-orbit interaction, where arguably the biggest success is the topological insulating family (BixSb1-x)2Te3, in which case a total compensation of the bulk conductivity can be achieved. Chapter 3 focuses on the spin polarization measurements in this topological insulator family. The in-plane spin polarization of all pristine compositions is extracted to be above 57%, and it reaches 83% for the composition which exhibits the most reduced bulk conductance. More importantly, carrier depletion has been demonstrated in the two end compositions, Bi2Te3 and Sb2Te3, by the observation of structure in the differential conductance when the superconducting tip is quenched in high-field. Furthermore, the influence of paramagnetic ion doping on the spin polarization values has been investigated. Both chromium and vanadium doping decrease the spin polarization values. The spin momentum locking in topological insulators provides spin polarization sign reversal by a mere switch in the polarity of a ballistic current, a functionality which can be very beneficial in future spin electronics devices. The magnetotransport and magnetic properties of the Fe60Al40 disordered composition have been investigated in Chapter 4. The disorder is induced by irradiation with Ne+-ions with variable fluences. The pristine Fe60Al40 is weakly paramagnetic, however, Fe-Al antisite defects lead to higher number of Fe-Fe nearest neighbours and ferromagnetic order with Curie temperature up to 620 K. The spin polarization is determined to increase from 10% in the non-irradiated to 46% in the sample with the highest irradiation dose. The spontaneous Hall angle is analyzed as well and extracted to reach 3%, a value close to the highest reported so far for ordinary magnetic compositions *. Furthermore, the saturation magnetization and the Curie temperature are investigated to increase systematically as a function of the irradiation dose. Chapter 5 focuses on Andreev reflection in high magnetic field. The main goal is extraction of the spin polarization sign through the observation of Zeeman-splitting in the superconductor quasiparticle density of states at temperature of 2 K. The experiments involve Nb-Ti superconducting wires and MgB2 superconducting films. Clear PCAR signal has been observed up to 9 T with Nb- Ti wires, unfortunately, with no Zeeman splitting. This provides opportunity for spin polarization investigation of novel ferromagnetic compositions where the spin polarization depends strongly on the applied magnetic field. High-field PCAR with MgB2 superconducting films have demonstrated clear Zeeman splitting of the density of states and the spin polarization sign has been correctly extracted as positive for Fe. High tunneling magnetoresistance (TMR) effect of 40% (at 10 K) has been achieved with compensated half-metallic ferrimagnet Mn2RuxGa in Chapter 6. The TMR has been investigated as a function of the applied bias and it exhibits positive-negative sign reversal which is typically not observed in standard magnetic tunnel junctions. Extensive analysis is given of the magnetotransport properties of the devices and the latter demonstrates that the TMR effect is currently limited by the imperfection in the MgO barrier (mainly caused by Mn diffusion). Crucially, appreciable TMR effect has been observed at the very compensation point of the Mn2RuxGa electrode where the magnetization is strictly zero. The latter is taken as a clear indication that the Fermi level spin polarization in this composition is determined by one of the Mn sublattices rather than by the overall magnetization. Importantly, the devices have demonstrated high magnetic field immunity (at least 0:5 T) in broad temperature range (10 K-300K), a property which will be critical in future high areal density magnetic random access memories. Each result chapter finishes with a short conclusion and a more in-depth overview is given at the end of the thesis.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin